2020
DOI: 10.4236/ojim.2020.104032
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of General Practitioners in Cotonou about Systemic Lupus Erythematosus

Abstract: Introduction: Patients with Systemic Lupus Erythematosus (SLE) are seen late in specialized medical consultation in Benin. The objective of this work was to assess general practitioners' knowledge in Cotonou about SLE. Materials and Methods: This work was a cross-sectional study that was led in the city of Cotonou from July 1 to September 30, 2017. In the study population, we have general practitioners who practice in the city. Data collection was set in response to a self-questionnaire. Result: The survey inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…According to Art et al, many GPs are concerned about their lack of expertise and experience in dealing with SLE, despite technological advancements in diagnosis, and hence tend to overestimate the disease's possible impact on patients [ 19 ]. A recent study done in Cotonou, Benin reported similar findings as our results where the majority of the GPs had limited knowledge about SLE [ 16 ]. In another study, cutaneous SLE was reported to be one of the most difficult diagnoses for GPs compared to other skin disorders [ 20 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…According to Art et al, many GPs are concerned about their lack of expertise and experience in dealing with SLE, despite technological advancements in diagnosis, and hence tend to overestimate the disease's possible impact on patients [ 19 ]. A recent study done in Cotonou, Benin reported similar findings as our results where the majority of the GPs had limited knowledge about SLE [ 16 ]. In another study, cutaneous SLE was reported to be one of the most difficult diagnoses for GPs compared to other skin disorders [ 20 ].…”
Section: Discussionsupporting
confidence: 90%
“…It has been noted that general practitioners (GPs) correctly diagnosed only 11% of SLE cases presented in clinical scenarios, far fewer than rheumatologists [ 15 ]. Furthermore, SLE awareness research in Cotonou, Benin demonstrated that the majority of GPs had minimal comprehension and awareness of the clinical and diagnostic criteria for SLE, while another study in China discovered that more than half of them were unaware of SLE [ 16 , 17 ]. Despite several studies on the Saudi general population's comprehension of SLE, no studies on PHCPs' understanding of SLE have been conducted in the Kingdom of Saudi Arabia (KSA).…”
Section: Introductionmentioning
confidence: 99%
“…A clear female predominance with a male to female sex ratio of 0.09 was found. This female predominance was also found by several other authors [5][6][7][8][9].…”
Section: Discussionsupporting
confidence: 88%
“…Systemic inflammatory diseases are little known and often difficult to diagnose in sub-Saharan Africa. In a study conducted in Cotonou in 2017, 91.4% of general practitioners were unaware of systemic lupus [6]. In this series, the mean age was 44 + 12 years with extremes from 24 to 64 years.…”
Section: Discussionmentioning
confidence: 67%
“…Awareness must be raised among patients and primary care physicians for early consultation and referral to an appropriate health center at the first sign of symptoms. Azon-Kouanou's study on general practitioners' knowledge of SLE in Cotonou (Benin), noted the lack of knowledge of the disease among primary care physicians [14].…”
Section: Discussionmentioning
confidence: 99%